Synthesis of lipase-immobilized CeO2 nanorods as heterogeneous nano-biocatalyst for optimized biodiesel production from Eruca sativa seed oil - Fatima, Anam; Mumtaz, Muhammad Waseem; Mukhtar, Hamid; Akram, Sadia; Touqeer, Tooba; Rashid, Umer; Ul Mustafa, Muhammad Raza; Nehdi, Imededdine Arbi; Saiman, Mohd Izham (MDPI, 2020)
Biodiesel has emerged as one of the most attractive alternative energy sources to meet the growing needs of energy. Many approaches have been adopted for biodiesel synthesis. In the present work, biodiesel was produced from non-edible Eruca sativa oil using nano-biocatalyst-catalysed transesterification. Nano-biocatalyst (CeO2@PDA@A. terreus Lipase) was developed via the immobilization of lipase on polydopamine coated ceria nanorods, and CeO2 nanorods were developed via a hydrothermal process. The mean diameter of nanorods were measured to be 50–60 nm, while their mean length was 150–200 nm. Lipase activity before and after immobilization was measured to be 18.32 and 16.90 U/mg/min, respectively. The immobilized lipase depicted high stability at high temperature and pH. CeO2@PDA@A. terreus Lipase-catalysed transesterification resulted in 89.3% yield of the product. Process optimization through response surface methodology was also executed, and it was depicted that the optimum/maximum E. sativa oil-based biodiesel yield was procured at conditions of 10% CeO2@PDA@A. terreus Lipase, 6:1 methanol/oil ratio, 0.6% water content, 35 °C reaction temperature, and 30 h reaction time. The fuel compatibility of synthesized biodiesel was confirmed via the estimation of fuel properties that were in agreement with the ASTM D standard. The nanorods and dopamine-modified nanorods were characterized by FTIR spectroscopy, SEM, and energy dispersive X-ray (EDX), while conversion of E. sativa oil to biodiesel was confirmed by GC/MS and FTIR spectroscopy. Conclusively, it was revealed that CeO2@PDA@A. terreus Lipase has potential to be employed as an emphatic nano-biocatalyst.